Knowledge, Practice and Attitude of Mothers for Ophthalmic Problems in Children in Rural Areas- A Cross-Sectional Study : Ophthalmic Problems in Children in Rural Areas - Khattak, Muhammad Iftikhar; Khan, Nasrullah; Tahir, Muhammad Younis; Rashid, Faisal; Iqbal, Rana Naveed; Sarfraz, Mariyam (Pakistan Journal of Health Sciences, 2023)
Early years are crucial for eye development. Parents are responsible for children’s eye care decisions. Objective: To assess the level of awareness and understanding of the practices among mothers regarding eye disorders and visual impairments in their children in rural areas. Methods: A cross-sectional study assessed the knowledge, practice, and attitude of rural mothers regarding eye problems in children. Results: 385 mothers participated in study. 47.3% were aged 41-50. 29.9% had completed graduation, while 16.1% were illiterate. Knowledge was scored from 2.00 to 14.00, with >7 being very knowledgeable, > 4 but ≤ 7 being somewhat knowledgeable, and ≤ 4 being not knowledgeable. Practice was scored from 0 to 5, with ≥ 3 indicating good practice, >1 to ≤ 3 indicating somewhat practicing, and ≤ 1 indicating poor practicing. Mothers had good knowledge of ophthalmic problems (99.4%). Attitude was scored from 0 to 10, with scores ≥ 6 indicating good attitude. Lack of time and convenience was the main reason for not seeking eye care (70.1%). Parents’ knowledge of ophthalmic problems significantly correlated with their attitude and practice (r = 0.546, p < 0.01 and r = 0.602, p < 0.01, respectively). Additionally, parents’ attitude was significantly correlated with their practice (r = 0.390, p < 0.01). Conclusions: Mothers’ knowledge, practice, and attitude play a key role in detecting and diagnosing the early signs of ophthalmic problems like refractive errors, strabismus, allergic conjunctivitis, and amblyopia.